The role of vitamin D in the human body and the benefits and risks of its supplementation - Dubel, Julia; Namroży, Natalia; Dubel, Robert; Czekaj, Aleksandra; Ruszel, Kinga; Zdun, Sylwia; Marciniak, Agnieszka; Grzywna, Natalia; Walczak, Patrycja; Walczak, Klaudia (Journal of Education, Health and Sport, 2022)
The prevalence of vitamin D deficiency in society and the growing awareness of related health problems have resulted in the widespread use of vitamin D supplementation. The source of vitamin D is skin synthesis with the participation of ultraviolet radiation (UVB) and its supply with the diet. The inability to cover the daily requirement for vitamin D without an additional source of vitamin D means that the society most often reaches for dietary supplements that do not have the properties of a medicinal product. The use of over-the-counter supplements, where the actual dose of the vitamin may differ from the dose declared by the manufacturers, may result in a lack of benefit from the food product when the vitamin D content is too low or lead to hypervitaminosis when the content is too high.